If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(b + 2) = 2(c + 3) Reorder the terms: 3(2 + b) = 2(c + 3) (2 * 3 + b * 3) = 2(c + 3) (6 + 3b) = 2(c + 3) Reorder the terms: 6 + 3b = 2(3 + c) 6 + 3b = (3 * 2 + c * 2) 6 + 3b = (6 + 2c) Add '-6' to each side of the equation. 6 + -6 + 3b = 6 + -6 + 2c Combine like terms: 6 + -6 = 0 0 + 3b = 6 + -6 + 2c 3b = 6 + -6 + 2c Combine like terms: 6 + -6 = 0 3b = 0 + 2c 3b = 2c Solving 3b = 2c Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '3'. b = 0.6666666667c Simplifying b = 0.6666666667c
| 14x+12y=178 | | 3(c-2)=(c+3) | | 6x^2y-2xy^2+3xy-5= | | 4x^2+3y^2-16x+12y+16=0 | | -x^3+6x^2-11x+6=0 | | -5x+27=3y | | n=4.7 | | sqrt(8x+1)+sqrt(3x-5)=sqrt(7x+4)+sqrt(2x-2) | | x=16+-9(2) | | 3x+2y=7whatisx | | 6x-8=20x-22 | | 3(16+-9y)+8y=10 | | (5b-5d)(5b+4d)= | | (4x^2)+(3y^2)-16x+12y+16=0 | | x=16+-9(1) | | x+2y+2z-5=0 | | 7+3(2+x)=28 | | 5y+3y^2=2 | | x^2+2x=y^2 | | (3xy+2z)(2xy-3z)= | | 6(3+-9y)+8y=-28 | | x^3-y^3+216=18y(-x) | | 3x^2+30x-17=-122 | | -14=4z | | log(2x-10)-log(10)=1 | | 10xy^2=0 | | 9xn=-27 | | -5+2x^2=-5x | | 3=7x+2 | | X^2+3xy-2x+5=0 | | -7y-3=2-6y | | 6((x-1)(x-1)-(x^2-1))+2(15-x)=0 |